Diagnóstico comunitario de salud del Barrio San Jacinto sector III y IV, septiembre-diciembre de 2013 - Moreno Paute, Mayra Alejandra (2013)
This research "COMMUNITY HEALTH DIAGNOSIS BARRIO SAN JUAN, SEPTEMBER - DECEMBER 2013" aims to: Perform diagnostic Community Hospital catchment area University of Motupe with the respective epidemiological profile and talking map, as a basis for the formulation of development projects in health sector so that sustainability of the proposed work of the health unit will be provided. Provide specific nursing services, designed to ensure the exercise of the right to health of disadvantaged groups as a means of community outreach and linking strategy with the health service. The study is descriptive in a universe of 38 families and 129 inhabitants, among the most relevant data are highlighted, that all families are located in medium risk, the level of education is outstanding basic and high school, one was found illiterate corresponding to head family, among schoolchildren and adolescents large part of them have good nutritional status in regard to sexually active women, the rhythm method is the most widely used family planning. Regarding the epidemiological profile is highlighted, chronic diseases and disabilities which allowed the update of the classification of catastrophic illnesses and disabilities. With the results it is recommended to teams that pose health strategies to improve the situation of the community, insisting that no families entered this study. The information is consolidated, using tables and graphs to reach the final lifting of talking map, which was supported by the physical map that was done throughout the day in the community. Key words: Health Study, Research Area "San Juan", community, situational.